Formulación del plan de gestión integral de residuos sólidos del Supermercado Mercatodo S.A - Sede Floresta (2018)
Through the elaboration of this plan it was intended to know the current situation of each component of the integral management of solid waste in the supermarket "Comercializadora Floralìa S.A - Floresta" by means of a detailed diagnosis within the different areas where waste is generated. Among the results, it was found that the supermarket generates approximately 45,518Kg of solid waste per month, of which 59% are waste with potential for use through composting processes and 39.4% are waste with economic potential through commercialization processes. Additionally, adjustments must be made to existing UAR storage units in accordance with Decree 2981 of 2013. After the analysis of the results obtained from the process of its origin until its final disposal of solid waste, five programs were established to structure the Comprehensive Solid Waste Management Plan - PGIRS and which are focused on the minimization of generation, separation At the source, utilization and valorization, in order to mitigate and reduce the environmental impacts that originates during the productive process of the supermarket, it should be noted that the effectiveness of these programs is in the participation of all the actors involved in the management of the waste in the different areas of the supermarket.